Demodex Blepharitis: A Survey-Based Approach to Investigate Knowledge, Attitudes, and Practices Among Optometrists in India - Sharma, Nikhil; Martin, Eilidh; Pearce, Edward Ian; Hagan, Suzanne; Purslow, Christine (Clinical optometry (Auckland), 2023)
To investigate the knowledge, attitudes, and practice towards Demodex blepharitis among optometrists in India. The study was conducted in the form of an online survey using Research Electronic Data Capture (REDCap). The survey link was distributed via direct e-mail and social media platforms, and it was comprised of 20 questions divided into two sections. The first section focused on the practitioners' demographics and their views on the general health of the eyelid. The second section of the survey was specific and aimed at obtaining information on identifying and treating Demodex blepharitis, and was only completed by those respondents who looked for Demodex mites. The survey was completed by 174 optometrists. The prevalence of blepharitis in the general population was judged by the respondents to be 40%, whereas the prevalence of Demodex mites was estimated to be 29%. Interestingly, the prevalence of Demodex mites in people with blepharitis was estimated to be 30%. This estimated prevalence was substantially lower than that reported in the literature on the subject. 66% of participants believed Demodex mites to be a significant cause of ocular discomfort, whereas only 30% of participants would intervene to diagnose and manage Demodex blepharitis in their patients. Optometrists differed in their preferred method of diagnosis and management of Demodex infestation in eyelids. The result of this survey suggests that Demodex blepharitis is a highly under-diagnosed condition in India, with nearly 30% of surveyed optometrists managing this condition. The study also observed a lack of awareness and consensus among surveyed optometrists with regards to diagnosis and appropriate treatment methods to control Demodex infestation in eyelids.